161 E assessing the impact of enhanced supportive care using the integrated palliative care outcome scale (ipos) at the christie nhs foundation trust. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Mola, Lisa La; Warren, Mark; Berman, Richard; Lilley, Shameem; Higham, Phil; Clare, Hannah
Abstract : Enhanced Supportive Care (ESC) is a new UK initiative that integrates supportive care within oncology. At its heart is better access to expertise in managing the adverse effects of cancer and cancer treatments to enhance the patient experience and reduce the need for hospital admission. ESC is award winning and has been recognised nationally by NHS England. The aim of this audit was to measure the impact of ESC using the Integrated Palliative Care Outcome Scale (IPOS). This is a validated tool that can be used in clinical audit, research and training to measure symptom burden. Method: 47 patients referred into the supportive care service, were randomly selected to complete the IPOS tool within 3 areas (inpatients, outpatients and trials unit) during May to October 2016. For all areas a baseline IPOS was completed prior to the initial assessment by supportive care. Subsequent IPOS were completed approximately 3 days later for inpatients. Outpatients and trial patients were reviewed at various time points depending on the timing of their follow up appointments. Outpatients had an average follow up of 41 days. Trial patients had an average follow up of 15 days. Results: The overall IPOS score is the sum of the score of each of the 17 questions and can range from 0–68. A reduction in the IPOS score demonstrates an improvement in physical and psychological patient symptom burden. 16 inpatients completed the IPOS and demonstrated a 50% improvement in overall mean symptom score. 5 experimental cancer medicine patients completed the IPOS and demonstrated a 49% improvement in overall mean score. 26 oncology outpatients completed the IPOS and demonstrated a 2.5% deterioration in overall mean score, demonstrating a possible correlation between frequency of supportive care review and symptom burden.